ESTIMATION OF CLAIM RESERVES USING THE CHAIN LADDER METHOD - Yoisangaji, Abdan Maulana Rohat; Pelu, Shelma Maharani; Wijaya, Jofie (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
One form and effort in dealing with all the risks that might occur in the future is insurance. In managing premiums paid by insurance participants, insurance companies must also consider unexpected claims that may occur in the future. Therefore, a method is needed that can be used by insurance companies to prepare claim reserves for the future. One method that is often used is the Chain Ladder method. This research aims to predict and estimate the claim reserves that insurance companies must prepare in the face of unexpected claims in the future. Based on the results of this study, the amount of claims that the company must prepare to deal with claims that may occur in 2020 is USD 1,110,879.00.